Community participation in the local rice security programs in Cailaco and Maliana sub-disctricts in Timor-Leste - Martins, Micael Soares Dos Santos; Dizon, Josefina T. (2017)
This study was conducted to analyze the factors affecting community participation in the rice security programs in Cailaco and Maliana, Timor-Leste in 2015. Respondents were 103 farmer-members randomly selected from seven farmer groups who worked in the rice programs. Socio-demographic and economic characteristics of the farmers were gathered. Primary data were collected using s structured survey questionnaire, supplemented with data from key informant interviews and focus group discussions. Secondary data were collected from government institutions and donor agencies. Results of the study show that farmers in Cailaco and Maliana have a mean age 44 years. They have been farming for about 20 years and members of farmers' group for four years. They have an average farm size of 2 ha with two parcels used for farming. They have very favorable attitude toward joining farmers' groups and very high trust toward co-farmers and farmers' groups. Using binary logistic regression, results show that the farmers were fully involved from project identification, planning, implementation, and up to monitoring and evaluation. It also reveals the socio-economic factors that affected the respondents' participation in the different phases of the programs. Year of membership in the farmers' group and trust in co-farmers significantly affected problem identification. Household size, adequate income for family support, and year of membership in farmers' group affected planning; age and financial resources were related to implementation; and age affected monitoring and evaluation.
Keywords: Rice security programs; Community development